Estimation Of Time Of Concentration Using Triangulated Irregular Network Method - Ewe, Teik Tsia (2015)
In Malaysia, Manual Saliran Mesra Alam (MSMA) has proposed two calculation methods to obtain areas between the isochrones that have been widely practiced at the moment. They are Grid method and Conventional method. However, these methods pose certain problems of their own. Although the Grid method is more detail and accurate when compared to the Conventional method, but that is extremely tedious and time consuming. Conventional method on the other hand is simpler to use. But, the results are not consistent. The results are very subjective because it depends on each user’s experience and judgement. Therefore, a new calculation method named Triangulated Irregular Network (TIN) method has been designed and developed in this research to improve the Time-Area method calculation. This method is computer based and thus the algorithm of TIN method was developed. The algorithm of the TIN method is explained in this research. A study site was constructed and eight sets of rainfall data were collected. All the results from each calculation method were verified with the collected site data to compare their accuracy. Investigation upon their efficiency and reliability were also presented in this research. The comparison showed that TIN method has higher accuracy. In the correlation coefficient comparison among the methods, TIN method has average accuracy of 0.988, Grid method has average accuracy of 0.936 and Conventional method has average accuracy of 0.948. When calculating their difference against the observed data in percentage, TIN method has average difference of 14.29%, Grid method has average difference of 25.67% and Conventional method has average difference of 24.52%. When using the peak flow comparison for the difference against the observed data, the results shows that TIN method has average difference of 3.48%, Grid method has average difference of 5.88% and Conventional method has average difference of 7.72%. Lastly, the methods were compared using the total flow volume. It was demonstrated that the TIN method has different of 0.19%, Grid method has different of 0.43% and Conventional method has different of 4.80% when compared to the observed data. The TIN method has the highest accuracy and reliability among the three methods. Besides, this research also showed that the newly developed TIN method algorithm is easier to use, less time consuming and more reliable.